France : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for France. (IMF Staff Country Reports; Country Report ;, 2008)
France's near-term economic outlook is moderately positive, but clouded by risks from the global environment. The government's reformist intentions provide an historic opportunity to place France onto a sustained higher growth path with greater opportunities for all. Economic policy should address the root cause of faltering growth performance. Further goods and services market reforms will boost potential output and consumer welfare. Fiscal policy should be vigilant to the risk of slippage in the fiscal deficit. The ongoing expenditure and tax policy reviews have been commended.